Aktivitas Antioksidan dan Kandungan Komponen Bioaktif Sari Buah Namnam - Adawiah Adawiah; Dede Sukandar; Anna Muawanah (Jurnal Kimia Valensi, 2015)
Antioxidant is a compoud  inhibit that have an important role in protecting health due to it can absorb free radical molecules and inhibit oxidative reaction which cause anykinds of diseases. This study aims to determine the chemical compositition and antioxidant  activity of namnam juice, characteristic of namnam. In this experimental, proximat analysis, TPC, TFC, Vitamin C, antioxidant activity were evaluated. Namnam juice contains 996.03 mg/L of phenolics, 421.09 mg/Lof flavonoids, 121.44 mg/100mL of vitamin C and high antioxidant activity with IC50 5µL/mL.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3155.